Effect of gonadotropin-releasing hormone agonist treatment on near final height in girls with central precocious puberty and early puberty - Eun Hye Yang; Ha Young Jo; Su Jeong Park; Hye Won Yoo; Soo-Han Choi; Hye-Young Kim; Kyung Hee Park; Young Mi Kim; Min Jung Kwak (Korean Society of Pediatric Endocrinology, 2023)
Purpose The aim of this study was to examine whether gonadotropin-releasing hormone (GnRH) agonist treatment is effective in preserving final height in patients with central precocious puberty (CPP) or early puberty (EP). Methods The medical records of 40 patients with CPP and 206 patients with EP who completed GnRH agonist treatment following diagnosis were analyzed retrospectively. Height and height standard deviation (height SDS) scores based on bone age (BA) were measured and calculated at baseline, after treatment completion, and at final follow-up to compare changes within and between groups. Predicted adult height (PAH) was estimated by the height corresponding to height SDS for BA in girls at 18 years 11 months of age based on the growth chart. Results PAH at baseline did not differ significantly between the CPP group (153.67±4.95) and the EP group (154.77±3.72). In the CPP group, PAH significantly increased at treatment completion (156.01±4.61) and at final follow-up (158.52±6.04) compared to baseline. In the EP group, PAH significantly increased at treatment completion (157.7±3.60) and at final follow-up (159.31±4.26) compared to baseline. The increase in PAH at all timepoints compared to baseline did not significantly differ between the CPP and EP groups. Conclusions Both CPP and EP groups had significantly greater PAH after treatment, with no difference in the amount of increase between groups. These results show that GnRH agonist treatment can help increase final height even in patients diagnosed with EP after the age of 8 years.